Amino acid release from the rat oral pontine reticular nucleus across the sleep-wakefulness cycle - Hasegawa, T; Azum, S; Inoué, S (Journal of medical and dental sciences, 2000)
To elucidate a functional involvement of amino acids in the regulation of vigilance states, we investigated time-course changes of glycine (Gly), glutamate (Glu), and glutamine (Gln) in the extracellular fluid of the oral pontine reticular nucleus (PnO) in freely behaving rats by an in vivo microdialysis technique. The average concentration of Gly in dialysates collected during rapid eye movement sleep (REMS) was significantly higher than that collected during wakefulness (W) and non rapid eye movement sleep (NREMS) under perfusion with normal artificial cerebrospinal fluid (aCSF). These state-dependent changes in Gly, however, failed to occur when the PnO was perfused with Ca2+-free aCSF. In contrast, the average concentration of neither Glu nor Gln exhibited state dependency under the perfusion with normal or Ca2+-free aCSF; however, the concentrations of all three amino acids showed no consistent time-sequential changes specifically in the first three minutes from the beginning of each vigilance state. Although it is suggested that in the PnO the average concentration of Gly was higher during REMS than during NREMS and W by a Ca2+-dependent mechanism, however, time-course changes in the amino acids are complicated and other mechanisms may also be influential.